Soil microbiota on disease tolerance in plants: A review (Research, Society and Development, 2021)
Interactions between plants and microbiota in the rhizosphere are one of the most important factors of plants sanity and soil fertility. The microbiota is complex, comprising numerous microorganisms, including arbuscular mycorrhizae and rhizobia are of great importance for plant health and productivity. The aim of this review was to characterize the symbiotic mycorrhizal and nitrogen-fixing bacteria and their relationship with plant diseases tolerance. Through a qualitative literature review, information on the effects of microbiota on plant disease tolerance was compiled. According to the reviewed literature, arbuscular mycorrhizae symbiosis, in phosphorus limiting condition, influences the vegetal community development, nutrients absorption, water relations and productivity. Mycorrhizae act as bio protectors against biotic and abiotic stress, beyond activation of plant defense mechanisms through induced resistance. Rhizobia can be considered biocontrol agents, contributing for plant sanity through the direct inhibition of phytopathogens, as observed by the mechanism of induced systemic resistance. Symbiosis stimulate the synthesis of metabolites that act protecting roots against phytopathogens through antibiosis and exudates liberation. It has concluded that both symbiosis contribute to more sustainable cultivation practices, to increase production and reduce the incidence of phytopathogens.